PENGARUH STANDAR KEAMANAN PANGAN TERHADAP EKSPOR PRODUK BIOFARMAKA INDONESIA - Purwono Nugroho; Muhammad Firdaus; Alla Asmara (IPB University, 2017)
There have been growing concerns about the effects of food safety standards on agricultural trade throughout the world. One of the food safety standards applied in international trade is the adoption of maximum residue limits of pesticides. This research uses panel gravity model to analyze the effect of maximum residual limit (MRL) of pesticides imposed by importing countries on export of Indonesia’s medicinal plant products. The results show that stringent food safety standards imposed by importing countries have a negative and statistically significant effect on Indonesia’s export of medicinal plant products. The results also show that volume of Indonesia’s medicinal plant products exports are influenced by real GDP of exporter and importer, population, production, economic distance, and ad valorem tariff. Keywords: food safety standard, Gravity model, Panel data, Medicinal plant products.